ANALISIS PENGGUNAAN INSTAGRAM AKUN @WEAR.MOUNA SEBAGAI MEDIA KOMUNIKASI PELANGGAN DALAM PENJUALAN ONLINE BUSANA MUSLIMAH (Studi Kasus pada Alumni Ma’had Al-Zaytun) - Dzulfahira Yusuf; Wiena Safitri; Muhammad N. Abdurrazaq (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research was conducted on the @Wear.mouna Instagram account, the target of which was the communication process that occurred on the @Wear.mouna Instagram account to customers in selling Muslim clothing. This research looks at the customer communication process carried out by @Wear.mouna in sales via Instagram social media which is managed by "Ma'had Al-Zaytun alumni". This research method uses a qualitative method which refers to dimensions of quality, value or significance which can only be conveyed through the use of words, language or writing. The data collection procedures carried out were interviews, observation and documentation with @Wear.mouna account owners, Admins and customers from @Wear.mouna stores. The research results show that the customer communication process carried out by @Wear.Mouna via social media Instagram which is managed by "Ma'had Al-Zaytun alumni" ensures a consistent presence with regular posts about new products, special offers and quality content related to Muslim women's fashion. . In each post, they pay attention to interactions with customers by replying to comments, greeting and answering questions quickly and friendly. The effectiveness of customer communication carried out by @Wear.mouna in sales via Instagram social media which is managed by "Ma'had Al-Zaytun alumni" has proven to be very high, with a proactive and responsive approach. Use. Mouna is able to maintain consistent customer engagement. Keywords: Communication, Instagram, Effectiveness;